BK polyomavirus genotyping at inter‐ and intra‐patient level in Spain. Issue 8 (13th June 2013) - Ledesma, J.; Bouza, E.; González‐Nicolás, M.A.; de Viedma, D. García; Rodríguez‐Sánchez, B.; Muñoz, P.
Abstract BK polyomavirus (BKV) is classified into four subtypes based on nucleotide variation of a 287 bp typing region in the VP1 protein. Most studies show that subtype I is predominant in different geographic settings, followed by subtype IV. However, BKV subtypes II and III are detected at low rates. In Spain, the prevalence of each subtype is not well known. The aim of this study was to identify the BKV subtypes from a selection of different types of patients and to determine whether different subtypes could be infecting the same patient. A hundred and twenty nine BKV‐positive urine samples were selected to amplify and sequence the typing region. Plasma specimens collected at the same time as the urine samples were also studied in 34 patients. A phylogenetic analysis and a study of substitutions in the VP1 protein were carried out with the sequences obtained. Subtype I was the predominant subtype detected in urine (61.2%) and plasma (38.2%) samples followed by subtype II. The analysis of paired samples showed that the subtype found in urine was different from that found in plasma in 10 patients. Fourteen BKV variants based on substitutions in VP1 were identified. The finding of compartmentalized infections involving different subtypes at different sites in some patients might mean specific and different selective pressure in each tissue. The potential involvement in the viral cycle of the different BKV variants found should be analyzed. J. Med. Virol. 85:1402–1408, 2013. © 2013 Wiley Periodicals, Inc.